Effects of porcine circovirus type 2 vaccination on nursery and finishing pig performance under a PRRS challenge - Shelton, N.W.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 2,571 barrows and gilts (PIC 337 × 1050) were used to determine the effects of porcine circovirus type 2 vaccine (PCV2) on nursery and finishing pigs that were challenged with porcine respiratory and reproductive syndrome (PRRS). Treatments were arranged in a 2 × 2 factorial design with main effects of gender (barrow or gilt) and vaccine (PCV2 vaccinates or non-vaccinates). Vaccinated pens received 2 doses of commercial PCV2 vaccine (Circumvent PCV, Intervet Inc., Millsboro, DE) according to label directions on d 1 and 22 in the nursery. All pigs were also inoculated on d 30 with serum containing PRRS virus as part of this production system’s protocol. Barns were double stocked from d 0 to 51. On d 51, gilts were moved to an adjacent facility and barrows were split into 2 pens. In the period after the initial PCV2 vaccination (d 0 to 15), no difference in ADG, ADFI, or F/G was observed (P > 0.13) between genders or between vaccinates and non-vaccinates. However, in the period after the second PCV2 vaccination (d 15 to 29), vaccinated pigs had decreased (P < 0.02) ADG compared with non-vaccinates as a result of decreased (P < 0.04) ADFI. Gilts also had increased (P < 0.04) ADG and ADFI compared with barrows. In the period after all pigs were inoculated with PRRS virus (d 29 to 50), PCV2 vaccinates had improved (P < 0.001) F/G over non-vaccinates and a trend (P < 0.08) for improved ADG. Gilts had poorer (P < 0.01) F/G compared with barrows from d 29 to 50. Over the entire 50-d nursery portion of the study, no differences were observed (P > 0.61) for ADG, ADFI, or final weight among gender or PCV2 vaccinates and non-vaccinates. However, F/G was improved (P < 0.001) with PCV2 vaccination. Pig weights on d 71 and 99 were increased (P < 0.001) in vaccinates compared with non-vaccinates, and barrows had increased (P < 0.001) BW compared with gilts on d 99. At the conclusion of the study (d 132 for barrows and d 142 for gilts), the percentage of pigs remaining on test was decreased (P < 0.001) in non-vaccinated pens compared with vaccinated pens (70.2% vs. 94.7%, respectively). This study suggests that despite the decrease in performance related to the second vaccination of PCV2, the second vaccination improved final performance and decreased the number of removals due to the PRRS health challenge.
Keywords: Disease challenge; Porcine circovirus type 2 (PCV2) vaccine; Swine